RNA-binding protein altered expression and mislocalization in MS. Issue 3 (May 2020) - Masaki, Katsuhisa; Sonobe, Yoshifumi; Ghadge, Ghanashyam; Pytel, Peter; Lépine, Paula; Pernin, Florian; Cui, Qiao-Ling; Antel, Jack P.; Zandee, Stephanie; Prat, Alexandre; Roos, Raymond P.
Abstract : Objective: To determine whether there are nuclear depletion and cellular mislocalization of RNA-binding proteins (RBPs) transactivation response DNA-binding protein of 43 kDa (TDP-43), fused in sarcoma (FUS), and polypyrimidine tract–binding protein (PTB) in MS, as is the case in amyotrophic lateral sclerosis (ALS) and oligodendrocytes infected with Theiler murine encephalomyelitis virus (TMEV), we examined MS lesions and in vitro cultured primary human brain–derived oligodendrocytes. Methods: Nuclear depletion and mislocalization of TDP-43, FUS, and PTB are thought to contribute to the pathogenesis of ALS and TMEV demyelination. The latter findings prompted us to investigate these RBPs in the demyelinated lesions of MS and in in vitro cultured human brain–derived oligodendrocytes under metabolic stress conditions. Results: We found (1) mislocalized TDP-43 in oligodendrocytes in active lesions in some patients with MS; (2) decreased PTB1 expression in oligodendrocytes in mixed active/inactive demyelinating lesions; (3) decreased nuclear expression of PTB2 in neurons in cortical demyelinating lesions; and (4) nuclear depletion of TDP-43 in oligodendrocytes under metabolic stress induced by low glucose/low nutrient conditions compared with optimal culture conditions. Conclusion: TDP-43 has been found to have a key role in oligodendrocyte function and viability, whereas PTB is important in neuronal differentiation, suggesting that altered expression and mislocalization of these RBPs in MS lesions may contribute to the pathogenesis of demyelination and neurodegeneration. Our findings also identify nucleocytoplasmic transport as a target for treatment.